Concordance of health states in couples: Analysis of self-reported, nurse administered and blood-based biomarker data in understanding society - Apostolos Davillas; Stephen E. Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2016)
We use a range of self-reported health measures, nurse-administered health measures and blood-based biomarkers to examine the concordance between the health states of partners in marital/cohabiting relationships. A lifecourse model of cumulative health exposures is used to interpret the empirical pattern of between-partner health correlation in relation to the elapsed duration of the relationship. This allows us to distinguish non-causal homogamy correlation arising from assortative mating, from potentially causal effects of shared lifestyle factors. We find important differences between the results for different health indicators, with strongest homogamy correlations observed for adiposity, associated biomarkers like blood pressure, heart rate, blood sugar and cholesterol, and also self-assessed general health. We find no evidence of a "dose-response relationship" for marriage duration, and show theoretically that this implies - perhaps counterintuitively - that shared lifestyle factors and homogamous partner selection make roughly equal contributions to the concordance we observe in most of the health measures we examine.
Keywords: C2; C8; I10; 330; Biomarkers; Health; Homogamy; Spousal concordance; Understanding Society